2012
DOI: 10.7452/lapl.201210055
|View full text |Cite
|
Sign up to set email alerts
|

``Entangled'' free-induction decay in CdS crystal under two-photon excitation by two crossed laser beams

Abstract: A new method of two-photon excitation of femtosecond signals of "entangled" free induction decay (EFID) by two crossed 790-nm laser beams in a CdS crystal at room temperature has been realized for the first time. This "entangled" (through the wave vectors) coherent response appears only in the case when the photons involved to the process of twophoton excitation of the sample belong to the different laser beams. This technique allows one to separate the EFID signal from the exciting femtosecond pulses and to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Where the notation 'CFID' stands for 'correlated free induction decay'. This expression coincides with final formula of [3]. Summing over the integrating over solid angle we obtain [10,11]…”
Section: Femtosecond Correlated Photon Echo Signalssupporting
confidence: 80%
See 1 more Smart Citation
“…Where the notation 'CFID' stands for 'correlated free induction decay'. This expression coincides with final formula of [3]. Summing over the integrating over solid angle we obtain [10,11]…”
Section: Femtosecond Correlated Photon Echo Signalssupporting
confidence: 80%
“…In Leontiev et al [3] the signals of the correlated free induction decay (CFID) generated in a CdS crystal under two-photon excitation by femtosecond 793 nm radiation of a Ti:sapphire laser at room temperature were predicted. Two laser beams propagating in the directions k 1 and k 2 at an angle of 60° to each other act on the same region of the CdS film inducing two gratings of nonequilibrium electric polarization − k k…”
Section: Introductionmentioning
confidence: 99%
“…In [5] we predicted the possibility of correlated free induction decay (CFID) signal generation under two-photon excitation of a CdS semiconductor crystal by femtosecond 800 nm radiation of a Ti:sapphire laser in the directions of wave vectors k 1 and k 2 oriented at an angle of 60° to each other. This optical transient phenomenon is formed in superposition states.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the situation is more complicated because of the two-and three-photon modes of the excitation by crossed femtosecond laser beams. The presence of the angle of 60° between the wavevectors of the first k1 and the second k2 exciting pulses leads, according to [7], to the emitting of the coherent CSF signals in the mutually opposite directions [8]. Earlier, in [9], it was experimentally shown that one needs the three-photon mode in order to excite the electrons of such structures by the radiation of this laser.…”
mentioning
confidence: 99%